DEVELOPMENT OF A MATHEMATICS MODULE ON INFINITE LIMITS OF ALGEBRAIC FUNCTIONS TO ENHANCE STUDENTS’ CRITICAL THINKING SKILLS - Deny Hadi Siswanto; Kintoko Kintoko; Tarso Tarso; Rohmanur Mala; Rif'an Efendi (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to develop a mathematics module on the infinite limit material of algebraic functions to improve critical thinking skills of phase-F students at SMA Muhammadiyah 1 Sleman. The study used the ADDIE development model which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through material and media expert validation questionnaires, student response questionnaires, and pretest and posttest tests. The validation results showed that the module was classified as very valid, with an average score of 71 from material experts and 103 from media experts. The student response questionnaire produced a practicality score of 72.6, indicating that the module was practical to use. The effectiveness test was carried out using the normality test and paired sample t-test using SPSS-25, which showed a significant increase (p <0.05) in student learning outcomes. The average pretest score of 58.22 increased to 84.27 in the posttest, with an n-Gain value of 0.64 which is classified as moderate. This module also improved scores on all indicators of students' critical thinking. Thus, the developed e-module is declared valid, practical, and effective in improving students' conceptual understanding and critical thinking skills